Dianthus chinensis L.: The Structural Difference between Vascular Bundles in the Placenta and Ovary Wall Suggests Their Different Origin - Guo, Xue-Min; Yu, Ying-Ying; Bai, Lan; Gao, Rong-Fu (Frontiers in Plant Science, 2017)
Dianthus chinensis is a perennial herbaceous plant with great ornamental, botanical, ecological, and medicinal value. The pistil of D. chinensis is composed of two fused carpels with free central placenta and two separate styles. The placenta is a columnar structure extending about two-thirds the length of the maturing fruit, which is typical of the Caryophyllaceous. Traditionally, free central placenta is thought to have evolved from axial placenta by septal disappearance, and axial placenta to have occurred through fusion of conduplicate carpels with marginal placenta. However, the traditional opinion is becoming more and more inconsistent with the new data gained in recent research of angiosperm systematics. To clarify the origin of D. chinensis pistil, the present anatomical study was carried out. The results show that the vascular system of placenta is independent to that of the ovary wall in D. chinensis. Moreover, in the central part of placenta there are one or two amphicribral bundles, and correspondingly numerous ones in the pistil which supply the ovules/seeds. It is obvious that the central amphicribral bundles in placenta are comparable to the counterparts in branches but not to those in leaves or their derivatives. Therefore, it is reasonable to deduce that the placenta of D. chinensis was not derived from conduplicate carpels through fusion of collateral vascular bundles, and actually a floral axis with ovules/seeds laterally adhering. On the contrary, the ovary wall was the lateral appendages of the floral axis. The result of the present study is completely in agreement with Unifying Theory, in which the placenta is taken as an ovule-bearing branch. Except for D. chinensis, the similar vascular organization has been observed in placenta of numerous isolated taxa. But till now, it is uncertain that whether this vascular organization pattern is popular in the whole angiosperms or not. More intensive and extensive investigations are needed.